Antidiabetic activity of methanolic extract of hibiscus cannabinus in streptozotocin induced diabetic rats - T.SUNDARRAJAN; T.RAJ KUMAR; E.UDHAYAKUMAR; M.SEKAR; M.K.SENTHIL KUMAR (International Journal of Pharma and Bio Sciences, 2010)
The aim of present study was to evaluate antidiabetic activity of methanolic extract of Hibiscus cannabinus; family Malvaceae leaves in streptozotocin induced diabetic rats. The alcoholic extract of Hibiscus cannabinus was studied for antidiabetic activity in streptozotocin induced diabetic rats by oral administration of extract 400mg/kg body weight for 15 days. The effect was compared with oral dose of 0.5mg/kg Glibenclamide. The determination of blood glucose level by GOD-POD kit method. The result shows the alcoholic extract of Hibiscus cannabinus leaves significantly lowered the blood glucose of hyperglycemic rats. From the toxicity study it was observed that methanolic extract of Hibiscus cannabinus was nontoxic up to 5g/kg body weight and phytochemical study showed the presence of phytosterols, flavonoids and glycosides. It is concluded that Hibiscus cannabinus leaf extract has significant antidiabetic activity, which lowered the fasting blood glucose level in Streptozotocin induced diabetic rats.